Long-term hypoxia modulates depolarization activation of BKCa currents in fetal sheep middle cerebral arterial myocytes - Nelapudi, Nikitha; Boskind, Madison; Hu, Xiang-Qun; Mallari, David; Chan, Michelle; Wilson, Devin; Romero, Monica; Albert-Minckler, Eris; Zhang, Lubo; Blood, Arlin B.; Wilson, Christopher G.; Puglisi, Jose Luis; et al. (Frontiers in Physiology, 2024)
IntroductionPrevious evidence indicates that gestational hypoxia disrupts cerebrovascular development, increasing the risk of intracranial hemorrhage and stroke in the newborn. Due to the role of cytosolic Ca2+ in regulating vascular smooth muscle (VSM) tone and fetal cerebrovascular blood flow, understanding Ca2+ signals can offer insight into the pathophysiological disruptions taking place in hypoxia-related perinatal cerebrovascular disease. This study aimed to determine the extent to which gestational hypoxia disrupts local Ca2+ sparks and whole-cell Ca2+ signals and coupling with BKCa channel activity.MethodsConfocal imaging of cytosolic Ca2+ and recording BKCa currents of fetal sheep middle cerebral arterial (MCA) myocytes was performed. MCAs were isolated from term fetal sheep (∼140 days of gestation) from ewes held at low- (700 m) and high-altitude (3,801 m) hypoxia (LTH) for 100+ days of gestation. Arteries were depolarized with 30 mM KCl (30K), in the presence or absence of 10 μM ryanodine (Ry), to block RyR mediated Ca2+ release.ResultsMembrane depolarization increased Ry-sensitive Ca2+ spark frequency in normoxic and LTH groups along with BKCa activity. LTH reduced Ca2+ spark and whole-cell Ca2+ activity and induced a large leftward shift in the voltage-dependence of BKCa current activation. The influence of LTH on the spatial and temporal aspects of Ca2+ sparks and whole-cell Ca2+ responses varied.DiscussionOverall, LTH attenuates Ca2+ signaling while increasing the coupling of Ca2+ sparks to BKCa activity; a process that potentially helps maintain oxygen delivery to the developing brain.